Assessment of ocular services status for diabetic patients in Saudi Arabia - Majid A. Moafa (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Diabetes mellitus is estimated to be the seventh cause of death in the world and it is prevalent in Saudi Arabia about 23.9%. Moreover, individuals with diabetes-related eye complications accounted for about 35.3% of diabetics, and the trend was still on the rise. Objectives: This study aimed to assess the status of the ocular services for diabetic patients in Saudi Arabia. Methods: This study adopted a cross-sectional study design among healthcare professionals who provide ocular services including ophthalmologists, opticians, optometrists, and physicians. The study included 63 participants, composed of healthcare providers directly involved in providing ocular services in Saudi Arabia. A random sampling technique was used to select eye care provider clinics in the country. Data collection was done through closed-ended questionnaires and observation techniques. The Data were checked for completeness and analyzed using SPPS version 24.0, and presented using tables. Results: The findings showed that seventy-one percent of the females disagreed that as long as blood sugars are well controlled, there is no need to worry about complications of diabetes mellitus while 35% of males disagreed with the statement. Most 84% of ophthalmologists stated that preventing visual impairments was a crucial matter that needed public attention. Most eye care providers performed dilated fundus examinations. Among the treatment options for diabetic retinopathy, laser coagulation was the most common treatment approach, accounting for 59%. Intravitreous corticosteroids were the least utilized treatment method for diabetic retinopathy. The choice of test to evaluate the diabetic patient’s eye depends on whether a doctor he/she is a physician, optometrist, optician, administration of the hospital, or ophthalmologist (p = 0.004). There was not enough evidence to claim that number of patients visiting in a month does not depend on the working place of a doctor (p=0.003). Conclusion: The number of patients who developed eye-related problems as a complication of diabetes was increasing due to missed diagnoses and lack of adequate optical care in Saudi Arabia. In addition, there were few optical clinics and opticians, compared to other eye professionals, and therefore this limits access to essential eye services by diabetic patients in Saudi Arabia.